THE EFFECT OF SHOPPING LIFESTYLE, DISCOUNTS AND PROMOTIONS ON IMPULSE BUYING AT SHOPEE MARKET PLACE - Sazuana, Yumi; Jumai , Jumai (Economics and Business International Conference Proceeding, 2024)
This research was conducted at the Faculty of Economics, University of Muhammadiyah Semarang, precisely on Jl. Kedungmundu no.18, Kedungmundu, Tembalang District, Semarang City, Central Java 50273. The aim is to find out how much the influence of Shopping Lifestyle, Discount and Promotion on Impulsive Buying in Shopee’s Market place. This research method uses a quantitative method. The population in this study is female students of the Faculty of Economics, University of Muhamadiyah Semarang. The sample in this study was 94 people. Sampling in this study uses probability sampling with simple random sampling (random sampling). The data analysis techniques used in the study are Descriptive Analysis, Validation Test, Reliability Test, Classical Assumption Test, Multiple Linear Analysis and Hypothesis Test using SPSS. The results of this study show that Shopping Lifestyle and Promotion have a positive and significant effect on Impulsive Buying, while Discount does not have a positive and significant effect on Impulsive Buying.